EFEK ANALGETIK EKSTRAK AKUADES DAUN MELINJO (Gnetum gnemon L.) PADA MENCIT PUTIH (Mus musculus L.) JANTAN DENGAN METODE INDUKSI ASAM ASETAT 1% - Dewi, Evelyne Citra; Sodik, Anwar; Khuluq, Husnul; Intiyani, Rafila (Fakultas Farmasi UMI, 2023)
Pain is an unpleasant sensory and emotional feeling, associated with tissue damage. Melinjo leaves (Gnetum gnemon L.) are a plant that is useful as a traditional medicine for reducing and treating diseases, one of which is pain. The use of traditional medicine has fewer side effects than chemical medicine. This study aims to determine the analgesic activity and best dose of melinjo leaf distilled water extract in male white mice induced by 1% acetic acid. This research is experimental research. The subjects of this research were 25 male white mice. Mice were divided into 5 treatment groups with each group consisting of 5 mice. The treatment groups consisted of negative control CMC-Na 1%, positive control, melinjo leaf aqueous extract group at doses of 50, 100, and 150 mg/kgBW. The pain inducer was given 1% acetic acid. Observations were made by observing the movements of mice to calculate the % of analgesic protection. The data that has been obtained is then tested using One Way Anova and Post Hoc LSD or Games-Howell statistical tests. The results obtained by melinjo leaf aqueous extract at a dose of 150 mg/kgBW had the best analgesic effect because it had the largest % protection, namely 66.89%, and provided a significant effect (p<0.05) in mice induced by 1% acetic acid. Melinjo leaf aqueous extract at a dose of 150 mg/kgBW had the best analgesic effect on male white mice which was declared significant (p<0.05) and the mean difference value was greater.